Investigation of the involvement of platelet-activating factor in the control of hypertension by aerobic training. A randomized controlled trial - Prado, João Paulo; Castro, Ana Emilia; Carvalho, Jonatan; Pereira, Daniele; Faccioli, Lúcia Helena; Sorgi, Carlos; Novaes, Rômulo; Silva, Silvia; Galdino, Giovane (Biology of Sport, 2024)
Although studies have demonstrated the effectiveness of exercise in controlling systemic arterial hypertension (SAH), the mechanisms involved in this effect are still poorly understood. Thus, this study investigated the impact of aerobic training on the relationship between platelet-activating factor (PAF) circulating levels and blood pressure in hypertensives. Seventy-seven hypertensive subjects were enrolled in this randomized controlled trial (age 66.51±7.53 years, body mass 76.17±14.19 kg). Participants were randomized to two groups: the intervention group (IG, n = 36), composed of hypertensive individuals submitted to an aerobic training protocol, and the control group (CG, n = 41), composed of non-exercised hypertensives. Body mass index, arterial blood pressure, quality of life, respiratory muscle strength, and functional capacity were assessed before and after 12 weeks. PAF and plasma cytokine levels were also evaluated respectively by liquid chromatography coupled with mass spectrometry and enzyme-linked immunosorbent assay. Aerobic training promoted a significant reduction in blood pressure while functional capacity, expiratory muscle strength, and quality of life, PAFC16:0 and PAFC18:1 plasma levels were increased in comparison to the CG ( p < 0.05). In addition, multiple correlation analysis indicated a positive correlation [F (3.19) = 6.322; p = 0.001; R 2 adjusted = 0.499] between PAFC16:0 levels and expiratory muscle strength after aerobic training. Taken together, our findings indicate that PAF may be involved in the indirect mechanisms that control SAH, being mainly associated with increased respiratory muscle strength in hypertensive subjects undergoing aerobic training.